Question #faff2

1 Answer
Oct 7, 2016

Answer:

#(axx10^n)/(bxx10^m) = a/b xx 10^(n-m)#

Explanation:

Using the property of exponents that #x^a/x^b = x^(a-b)#, suppose #a xx 10^n# and #b xx 10^m# are two numbers in scientific notation (i.e. #a, b in [1, 10)#) Then

#(axx10^n)/(bxx10^m) =a/b xx 10^n/10^m = a/b xx 10^(n-m)#

Note that #1/10 < a/b < 10#, meaning an additional #10^(-1)# may be multiplied #10^(n-m)# if we are writing the answer in scientific notation.

Some examples:

#(6 xx 10^5)/(2 xx10^9) = 6/2 xx 10^(5-9) = 3 xx 10^-4#

#(2 xx 10^7)/(5xx10^3) = 2/5 xx 10^(7-3) = 0.4xx10^4 = 4xx10^3#